Study on Linear Motor Vehicle Traction Energy Consumption of Guangzhou Metro Line 6 - DAI Bin; LI Xiaoxiao; WANG Suisheng; DENG Jun (机车电传动)
Linear motor vehicle energy consumption problem of Guangzhou metro line 6 was studied, and the too short inter-station distance and too much ramp and curved way were indicated to be the major cause of high energy consumption of the line 6 vehicle main line operation. The relevant linear motor vehicle energy consumption data and research conclusion could provide reference for vehicle energy consumption study and new railway lines design.